2014
DOI: 10.2139/ssrn.2509364
|View full text |Cite
|
Sign up to set email alerts
|

Rejection from the Disability Insurance Program and Dependency on Social Support

Abstract: Abstract. Recent studies find that many workers do not return to the labor force after their applications for Disability Insurance (DI) are denied. It is, therefore, important to understand how this group funds their consumption. This paper uses the Survey of Income and Program Participation linked to administrative data to examine the social support participation behavior of rejected applicants. By following cohorts of individuals from 10 years before to 10 years after filing for DI, this paper shows that rej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For the awarded applicants, in addition to the worsening of mental health leading to retirement, disability pension as an involuntary retirement is associated with emerged psychological symptoms [47][48][49]. A rejected pension may also create long-lasting stress [19,22], especially with additional financial challenges [15][16][17][18].…”
Section: Awarded and Rejected Applicants After The Pension Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the awarded applicants, in addition to the worsening of mental health leading to retirement, disability pension as an involuntary retirement is associated with emerged psychological symptoms [47][48][49]. A rejected pension may also create long-lasting stress [19,22], especially with additional financial challenges [15][16][17][18].…”
Section: Awarded and Rejected Applicants After The Pension Decisionmentioning
confidence: 99%
“…We aim to further understand the association between the disability pension process and the use of psychotropic drugs by including both awarded and rejected applicants. While the financial and labor market challenges for rejected disability pension applicants are clear [15][16][17][18], studies on mental health after the pension decision have been mostly qualitative [19,20]. In one of the rare quantitative studies, Ydreborg et al [21] found that after the pension decision, those who received a rejection had lower self-reported health, quality of life, and smaller social networks than awarded applicants.…”
Section: Introductionmentioning
confidence: 99%